In Vitro and In Vivo Effects of Radio- Frequency Electromagnetic Fields - Begimbetova , D. A.; Baiskhanova , D. M.; Matkarimov , B. T.; Shulgau , Z. T. (Eurasian Journal of Applied Biotechnology, 2020)
In recent years, there has been a massive distribution of mobile phones and Wi-Fi networks. In this regard, concerns about their potential effects on living organisms, including humans, are increasing. Despite earlier assumptions about the absence of harmful effects of short-term exposure to radio frequency electromagnetic fields emitted by mobile phones and Wi-Fi networks, there is now increasing evidence of the potentially harmful effects of electromagnetic fields on the human body through the induction of oxidative stress and damage to DNA structure. It is assumed that prolonged exposure to electromagnetic fields can cause the development of various pathological conditions in the human body, including oncological diseases, impaired cognitive functions and sleep, etc. This review analyzes and summarizes existing studies indicating various negative effects of radio frequency electromagnetic fields on human and animal cells. Since there is a large amount of conflicting data on the effect of electromagnetic fields on the human body, only further research can provide an answer to the possible negative effects of mobile phones and Wi-Fi networks usage.